Improving growth and productivity of tomato by some biostimulants and micronutrients with or without mulching - Ibrahim, K.H. Ghoniem, M.N. Helaly, A.A. Arafa, Heba M. (Journal of Phytology, 2018)
Two field experiments were doled out during 2014 and 2015 growing seasons to assess tomato growth and yield as affected by some biostimulants and micronutrients with or without mulching type. Certain physiological characters were also examined, plant height, the number of branches per plant chlorophyll a, nitrogen %, red fruit weight and total yield per plant as well as fruit firmness and ascorbic acid concentration in fruit was increased in tomatoes under black plastic mulch compared with bar soil. Application of either biostimulants or micronutrient used to increase all growth and yield characters as well as photosynthetic pigments, ions percentage, and fruit quality. Additive effects were shown under mulching, seaweed extract proved to be the most effective in this respect. It could be recommended that spraying tomato crop at 35 and 50 days from transplanting with 500 mg/l seaweed extract under clear or black plastic mulch in order for inducing the highest yield and improve fruit quality.